The synergistic effects of DNA-damaging drugs cisplatin and etoposide with a histone deacetylase inhibitor valproate in high-risk neuroblastoma cells - Groh, Tomas; Hrabeta, Jan; Khalil, Mohammed Ashraf; Doktorova, Helena; Eckschlager, Tomas; Stiborova, Marie (International journal of oncology, 2015)
High-risk neuroblastoma remains one of the most important therapeutic challenges for pediatric oncologists. New agents or regimens are urgently needed to improve the treatment outcome of this fatal tumor. We examined the effect of histone deacetylase (HDAC) inhibitors in a combination with other chemotherapeutics on a high-risk neuroblastoma UKF-NB-4 cell line. Treatment of UKF-NB-4 cells with DNA-damaging chemotherapeutics cisplatin or etoposide combined with the HDAC inhibitor valproate (VPA) resulted in the synergistic antitumor effect. This was associated with caspase-3-dependent induction of apoptosis. Another HDAC inhibitor trichostatin A and a derivative of VPA that does not exhibit HDAC inhibitory activity, valpromide, lacked this effect. The synergism was only induced when VPA was combined with cytostatics targeted to cellular DNA; VPA does not potentiate the cytotoxicity of the anticancer drug vincristine that acts by a mechanism different from that of DNA damage. The VPA-mediated sensitization of UKF-NB-4 cells to cisplatin or etoposide was dependent on the sequence of drug administration; the potentiating effect was only produced either by simultaneous treatment with these drugs or when the cells were pretreated with cisplatin or etoposide before their exposure to VPA. The synergistic effects of VPA with cisplatin or etoposide were associated with changes in the acetylation status of histones H3 and H4. The results of this study provide a rationale for clinical evaluation of the combination of VPA and cisplatin or etoposide for treating children suffering from high-risk neuroblastoma.
Keywords: DNA, Neoplasm; nádorové buněčné linie; DNA Damage; apoptóza; kaspasa 3; poškození DNA; Cisplatin; cisplatina; Drug Synergism; Cell Proliferation; Cell Line, Tumor; Neuroblastoma; Valproic Acid; histony; Histones; synergismus léků; Caspase 3; Humans; Etoposide; inhibitory histondeacetylas; Histone Deacetylase Inhibitors; DNA nádorová; etoposid; acetylace; proliferace buněk; kyselina valproová; Acetylation; neuroblastom; lidé; Apoptosis